2017
DOI: 10.1080/17474086.2017.1346470
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of hypomethylating agents

Abstract: Introduction: Epigenetic changes resulting from aberrant methylation patterns are a recurrent observation in hematologic malignancies. Hypomethylating agents have a well-established role in the management of patients with high-risk myelodysplastic syndrome or acute myeloid leukemia. In addition to the direct effects of hypomethylating agents on cancer cells, there are several lines of evidence indicating a role for immune-mediated anti-tumor benefits from hypomethylating therapy. Areas Covered: We reviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 73 publications
2
50
0
2
Order By: Relevance
“…High-dose decitabine is known to display cytotoxic effects. Recently, researchers have found that there was no correlation between methylation reversal of tumor suppressor genes and clinical response in some patients treated with decitabine, implying that demethylation drugs might have other unidentified mechanisms that need to be elucidated ( 49 , 50 ). The results of our study showed that Fer-1, DFO, necrostatin-1, and the former that has the most significant effect could reverse the growth-inhibitory effect of decitabine on SKM-1 and MUTZ-1, indicating that ferroptosis and necroptosis may be the main mechanisms of decitabine-induced cell death of MDS cells.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose decitabine is known to display cytotoxic effects. Recently, researchers have found that there was no correlation between methylation reversal of tumor suppressor genes and clinical response in some patients treated with decitabine, implying that demethylation drugs might have other unidentified mechanisms that need to be elucidated ( 49 , 50 ). The results of our study showed that Fer-1, DFO, necrostatin-1, and the former that has the most significant effect could reverse the growth-inhibitory effect of decitabine on SKM-1 and MUTZ-1, indicating that ferroptosis and necroptosis may be the main mechanisms of decitabine-induced cell death of MDS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic-targeting agents, particularly DNA methyltransferase inhibitors (DNMTIs), are being investigated in combination with anti-PD1 therapy in hematologic malignancies (2). Enhanced endogenous retroviral expression and cancer testis antigen expression induced by demethylation results in increased tumor recognition by immune cells (3)(4)(5)(6)(7). We have previously shown that ascorbic acid (AA) causes demethylation and corresponding increase in the hydroxymethylation fraction of both lymphoma and renal cell carcinoma cells by enhancing the activity of the Ten-Eleven Translocation (TET) enzymes (8,9).…”
mentioning
confidence: 99%
“…We hypothesized that AA may be an optimal demethylating agent for combination with anti-PD1 therapy as it has also been shown to enhance the function of immune cells such as natural killer (NK) cells, macrophages, and dendritic cells (11,12). In contrast, effects of DNMTIs on immune cells are inconsistent, with some studies indicating an inhibitory effect (3,(13)(14)(15)(16). Importantly, high-dose AA has been shown to be a promising anticancer agent in early-phase clinical trials and is not only well tolerated but appears to decrease the side effects of chemotherapy (17).…”
mentioning
confidence: 99%
“…The downregulation or loss of MHC expression, the genetic loss or silencing of antigen source protein are well-known immune escape mechanisms in cancer. This can be fairly extensive as described in haplo-identical transplants, where the loss of the entire mismatched haplotype can be observed (152). Elaborate strategies targeting MHC-associated peptides presented by different alleles and belonging to different haplotypes may be necessary to harness the therapeutic potential of T-cell immunotherapy against genetic variants translated into MHC-associated peptides.…”
Section: Perspectives and Clinical Integration Of T-cell Therapiesmentioning
confidence: 99%